If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2y + -2) * y = 5 Reorder the terms: 3(-2 + 2y) * y = 5 Reorder the terms for easier multiplication: 3y(-2 + 2y) = 5 (-2 * 3y + 2y * 3y) = 5 (-6y + 6y2) = 5 Solving -6y + 6y2 = 5 Solving for variable 'y'. Reorder the terms: -5 + -6y + 6y2 = 5 + -5 Combine like terms: 5 + -5 = 0 -5 + -6y + 6y2 = 0 Begin completing the square. Divide all terms by 6 the coefficient of the squared term: Divide each side by '6'. -0.8333333333 + -1y + y2 = 0 Move the constant term to the right: Add '0.8333333333' to each side of the equation. -0.8333333333 + -1y + 0.8333333333 + y2 = 0 + 0.8333333333 Reorder the terms: -0.8333333333 + 0.8333333333 + -1y + y2 = 0 + 0.8333333333 Combine like terms: -0.8333333333 + 0.8333333333 = 0.0000000000 0.0000000000 + -1y + y2 = 0 + 0.8333333333 -1y + y2 = 0 + 0.8333333333 Combine like terms: 0 + 0.8333333333 = 0.8333333333 -1y + y2 = 0.8333333333 The y term is -1y. Take half its coefficient (-0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -1y + 0.25 + y2 = 0.8333333333 + 0.25 Reorder the terms: 0.25 + -1y + y2 = 0.8333333333 + 0.25 Combine like terms: 0.8333333333 + 0.25 = 1.0833333333 0.25 + -1y + y2 = 1.0833333333 Factor a perfect square on the left side: (y + -0.5)(y + -0.5) = 1.0833333333 Calculate the square root of the right side: 1.040833 Break this problem into two subproblems by setting (y + -0.5) equal to 1.040833 and -1.040833.Subproblem 1
y + -0.5 = 1.040833 Simplifying y + -0.5 = 1.040833 Reorder the terms: -0.5 + y = 1.040833 Solving -0.5 + y = 1.040833 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + y = 1.040833 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + y = 1.040833 + 0.5 y = 1.040833 + 0.5 Combine like terms: 1.040833 + 0.5 = 1.540833 y = 1.540833 Simplifying y = 1.540833Subproblem 2
y + -0.5 = -1.040833 Simplifying y + -0.5 = -1.040833 Reorder the terms: -0.5 + y = -1.040833 Solving -0.5 + y = -1.040833 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + y = -1.040833 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + y = -1.040833 + 0.5 y = -1.040833 + 0.5 Combine like terms: -1.040833 + 0.5 = -0.540833 y = -0.540833 Simplifying y = -0.540833Solution
The solution to the problem is based on the solutions from the subproblems. y = {1.540833, -0.540833}
| 2x=7.1 | | q^2=-5 | | 5x+72y=1 | | 0=48x-.6x^2 | | y=3a+b | | 6x-50=2x+10 | | -4+6(-5k-6)=-130 | | 22x+9=25x | | 7-6n=55 | | 2x-4x-10=-20 | | 0=48t-.6t^2 | | 12n-4=12n-4 | | X(x+8)=8 | | [x-6]+18=41 | | 5x+2=10x-38 | | -0.68+1.7r=3.57 | | -5(-1-5b)=155 | | r^2-2v-48=0 | | 7x+9-5x=-11 | | C=KNYsolvey | | -0.68+1.7=3.57 | | 480=48x-.6x^2 | | 4y-3-6y= | | 480=48x-6x^2 | | 2x^2+2y^2+8x+12y+18=0 | | 5(4+3n)+3=98 | | (3x+5)(x+8)= | | -22=5x-x+10 | | 480=48x-.6t^2 | | -33=5(x+3)+7x | | 3x-2y+c=0 | | -11=-1-2b |